Nanofósiles calcáreos, duración y origen de ciclos caliza-marga (Jurásico tardío de la Cuenca Neuquina) - Scasso, R.A. (1999)
Calcareouos nannofosils, duration and origin of limestone-marl cycles (Late Jurassic, Neuquén Basin). A nannofossil association corresponding to Zone NJ20b was defined in the rhythmically interbedded limestones and marls of the Los Catutos Member, Vaca Muerta Formation. It confirmed the Late Middle Tithonian age, previously assigned on the basis of ammonites, to the beds which crop out in the locality of Zapala, Neuquén Province, Neuquén Basin. The stratigraphical resolution of the nannoflora was no better than that of the ammonite fauna, but a good correlation between zones can be established. This represents a powerful and useful tool for future biostratigraphical studies in the Neuquén Basin. On the basis of the ammonite and nannofossil zones, a period of 1 my was estimated for the deposition of the 25 m thick sequence of limestones and marls. From these data a high sedimentation rate (5 m/ka on average) was calculated. As a consequence, the duration of the individual limestone-marl cycles is about 20 ka on average, in good agreement with the precession period of the earth axis. Thus, rhythmic changes in sedimentation would be related to climatic changes driven by orbital forcing. © 1999 Asociación Geológica Argentina.